Strengthening The Management of Funeral Expenses System: Towards Digitalization and Sustainable Outcomes - Zarabizan Zakaria; Nor Hazlina Abdullah (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The study was conducted to identify current effectiveness of funeral expenses (khairat kematian) management system in Muslim community. Findings from the survey could lead to the development of a system that can provide excellent services and effective solutions to the funeral expenses management system in the Muslim community. A concise description of the common issues that need to be addressed has been detailed out using Ishikawa Fishbone Diagram. A survey using Google Form was chosen as a method of data collection. 60 respondents comprising various ages and states in Malaysia were involved in the survey. Ishikawa Fishbone Analysis tool was used to identify the causes that contribute to ineffectiveness of the funeral expenses management system. The outcomes of the responses obtained from the survey were analyzed using SWOT Analysis. There were several strategies and action plans suggested at the end of this project paper. These studies and outcomes will trigger macro and micro impacts in context of more effective communication network through an integrated mobile application system. In a nutshell, the proposed e-khidmat system is expected to be an effective solution to the funeral expenses management system.